Judge for yourself reading hyper-contemporary literature and book prize shortlists - Taylor-Collins, Nicholas (Abingdon, Oxon ; New York, NY : Routledge, Taylor & Francis Group, 2021)
Judge for Yourself guides interested and advanced-level readers through the challenge of judging the quality of hyper-contemporary literature. Whether reading the latest bestseller or the book that everyone is recommending, Judge for Yourself guides you through the challenge of the text. Reading the longlist of the 2019 International Dylan Thomas Prize through five chapters, Judge for Yourself introduces readers to current critical debates that inform engagement and the reading experience of hyper-contemporary writing. Topics covered include feminism, postcolonialism, critical race theory, queer theory, class, and book reviews. Each chapter includes introductory questions for the reader, and Judge for Yourself is accompanied by an exploration of book prize culture and the challenge posed by hyper-contemporary literature. Judge for Yourself puts judging firmly in the hands of the reader, and not the academic or professional reviewers.
Introduction: The Judgement of Dr J. Evans Pritchard, PhD; or, in praise of bad literature 1. Feminism; or, emasculating the canon 2. Postcolonialism and critical race theory; or, decolonising the canon 3. Queer theory; or, bending the canon 4. Class; or, dividing the canon 5. Reviews; or, popularising the canon Conclusion: The end of the hyper-contemporary
OCLC-licensed vendor bibliographic record.
Keywords: Literature, Modern -- 21st century -- History and criticism -- Theory, etc; Literary prizes; LITERARY CRITICISM / General